Micropatterned immobilization of membrane-mimicking polymer and peptides for regulation of cell behaviors in vitro. Issue 37 (6th June 2018) - Ma, Wenyong; Liu, Luying; Chen, Huiqing; Zhao, Yuancong; Yang, Ping; Huang, Nan
Abstract : The Ti-PDA-M/R(P) biomimetic micropattern was successfully fabricated with PMMPC-HD and GREDVY. The Ti-PDA-M/R(P) micropattern can regulate EC morphology, orientation and functions, and inhibit platelet adhesion and proliferation of SMCs. Abstract : To regulate the behaviors and functions of endothelial cells (ECs) on the biomaterials on titanium (Ti), a biomimetic micropattern (ridge/groove: 25/25 μm) of polymer of 2-methacryloyloxyethyl phosphorylcholine (polyMPC) and Gly-Arg-Glu-Asp-Val-Tyr (GREDVY) was fabricated. PMMPC (monomer contain MPC and methacrylic acid (MA)) containing carboxyl groups was chosen, and PMMPC was cross-linked with hexamethylene diamine through condensation reaction of amino and carboxyl. Simultaneously, the carboxyl groups of cross-linked PMMPC (PMMPC-HD) can react with amino groups of polydopamine which can adhered on many materials firmly. GREDVY was immobilized on polydopamine but not on PMMPC-HD because amino and carboxyl groups can react with catechol and amino groups of polydopamine. IR and 1 H NMR demonstrated that PMMPC-HD was successfully synthesized. And the QCM-D (quartz crystal microbalance with dissipation) and IR approved that PMMPC-HD and GREDVY can be immobilized on polydopamine (PDA). Platelet adhesion and whole blood adhesion on micropattern modificated with PMMPC and GREDVY (Ti-PDA-M/R(P)) showed better hemocompatibility than other samples. Endothelial cells were regulated in the direction of micropattern showing elongated ECs were closer to a healthy, athero-protective phenotype than ECs cultured in vitro without micropattern. NO and PGI2 release were upregulated. Simultaneously the number of SMCs on Ti-PDA-M/R(P) was the smaller that of other samples, which demonstrated that the Ti-PDA-M/R(P) had property of inhibiting SMCs proliferation to a certain extent.